PENGARUH KADAR BRAIN DERIVED NEUROTROPHIC FACTOR PADA HENDAYA KOGNITIF RINGAN TIPE AMNESTIK - Yuda Turana; Yvonne S Handayani (NEURONA, 2021)
Introduction: Several clinical studies have shown the relationship between brain-derived neurotrophic factor (BDNF) and amnestic type mild cognitive impairment (aMCI). A significant reduction in peripheral BDNF levels due to aging is a predisposing factor for clinical manifestations of dementia in the elderly. Aim: To determine the role of BDNF and the risk factors for aMCI. Methods: Cross-sectional study, comparative analytic in the elderly group with normal cognitive function and elderly with aMCI. The study used secondary data from the Atma Jaya Cognitive and Aging Research Project in the elderly group ≥ 60. There were 109 data on the elderly who met the criteria, and the elderly were divided into MCI, aMCI, nonamnestic, and normal cognitive function. Results: It was found that 46.7% of the subjects had aMCI. Most of the subjects were women (70.6%) with a mean age of 64.04±5.54 years, less than six years of formal education (40.4%), and over body weight (49.5%), systolic hypertension (4????.1%), and LDL levels ≥130 mg/dL (61.1%), and had a mean BDNF level of 3010 pg/mL. In the sub-analysis, female subjects with aMCI had a significantly lower mean BDNF than normal cognitive subjects (p=0.029). Discussion: There was no effect on BDNF levels, demographic characteristics, lipid profile, body mass index and blood pressure with the incidence of aMCI. In the female subpopulation, low levels of BDNF were associated with the incidence of aMCI Keywords: BDNF, elderly, mild cognitive impairment